Regulation of Flowering Time: When and Where? - Freytes, Santiago Nicolás; Canelo, Micaela; Cerdán, Pablo D. (Current opinion in plant biology, 2021)
In seasonal flowering, plants need to monitor environmental variables. A combination of photoreceptors and the circadian clock initiate signals that regulate a network of genes in the leaf vascular system which communicates through mobile FLOWERING LOCUS T (FT) proteins, with the shoot apical meristem (SAM). At the SAM, a second network of genes is turned on specifically in certain cell domains, established by a second mobile protein, TERMINAL FLOWER 1 (TFL1), to ensure that flowering signals are translated into floral meristems at the flanks of the SAM but without compromising the nature of the SAM itself. Here, we provide an update on recent findings about the integration of light signals upstream of FT and tissue-specific events that occur in the SAM to balance flower production with SAM endurance.